Organizational learning and benchmarking in university technology courses: A Brazilian experience. Issue 2 (22nd January 2019) - Rübenich, Nilson Varella; Dorion, Eric Charles Henri; Eberle, Luciene
Abstract : Purpose: The purpose of this paper is to analyze the management practices that contribute to single and double cycles of organizational learning in the vocational education of the Brazilian higher education technology courses (HETC), and to study the learning outcomes that result through the Brazilian Ministry of Education SINAES indicators. Design/methodology/approach: It consisted in both participant observation and quantitative phases. The participant observation phase included a benchmarking activity at École de Technologie Supérieure (ÉTS) de Montréal, to analyze and delimitate their practices for the preparation of the second phase, test the hypotheses by means of modeling of structural equations. Findings: The key practices that contribute to organizational learning in the Brazilian HETC were identified through a benchmark activity at ÉTS by using a quantitative research scheme of single cycles of organizational learning, and further in correspondence with the Brazilian criteria (SINAES-Ministry of Education). Research limitations/implications: The extent of the sample is concentrated in the southern region of Brazil (Rio Grande do Sul, Santa Catarina and Paraná), limiting its representativeness to a regional basis. Practical implications: Practices that contribute to organizational learning are a counterpoint and a complement of the Brazilian Ministry of Education SINAES indicators, which value the formalization of those courses and the future actions in the Brazilian universities. Social implications: The study re-inforces the importance of organizational learning for the development of excellence in Brazilian HETC. Originality/value: The results contribute to build analysis frameworks on the relationships between management practices, organizational learning, benchmarking and organizational outcomes, particularly in the management of the technology courses and for Brazilian universities.